2011
DOI: 10.1016/j.ijadhadh.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma surface modification of titanium for high temperature adhesive bonding

Abstract: Abstract:In this investigation surface treatment of titanium is carried out by plasma ion implantation under atmospheric pressure plasma in order to increase the adhesive bond strength. Prior to the plasma treatment, titanium surfaces were mechanically treated by sand blasting. It is observed that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Therefore, single lap shear adhesive bond strength of plasma-treated titanium alloy is comparable to that of chemically modified titanium surface. [16] 1. Atmospheric pressure plasma treatment Polyimide sheets were plasma treated using TIGRES Plasma-BLASTER MEF equipment with operating voltage of 230 V and frequency of 60 Hz.…”
Section: A Materialsmentioning
confidence: 99%
“…Therefore, single lap shear adhesive bond strength of plasma-treated titanium alloy is comparable to that of chemically modified titanium surface. [16] 1. Atmospheric pressure plasma treatment Polyimide sheets were plasma treated using TIGRES Plasma-BLASTER MEF equipment with operating voltage of 230 V and frequency of 60 Hz.…”
Section: A Materialsmentioning
confidence: 99%
“…Elements made of titanium and its alloys used in these industries must very often be joined. It can be observed that titanium elements are more and more widely joined by adhesive bonding, a technique that constitutes an alternative to traditional joining methods [4][5][6][7][8][9][10]. Adhesive bonding is used for joining materials with specified properties, which are then used for making elements of various shapes located in various places of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is more frequently used, because in sulfuric acid etching, one can observe hydrogen adsorption by titanium. In addition to this, surface can also be prepared by plasma treatment [8,10,16,22]. Surface preparation of titanium and titanium alloys for adhesive bonding usually involves the use of mechanical treatment [8,15,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloys have been increasingly widely used in aviation, aerospace, shipbuilding and other industrial departments whereas the main use of TiO 2 is as a white powder pigment used in products such as paints, coatings, plastics, paper, inks, fibers, food and cosmetics [Akram et al, 2011;Chunxiang et. Al., 2011].…”
Section: Introductionmentioning
confidence: 99%